Triple, simultaneous, very late coronary stent thrombosis - Silva-Vieira, M. (2013)
Abstract Coronary artery stent thrombosis is an uncommon but potentially catastrophic complication. The risk of very late stent thrombosis (VLST) raises important safety issues regarding the first generation of drug-eluting stents (DES). Although several complex mechanisms for VLST have been suggested and various predictors have been described, its pathophysiology is not completely understood and it is not known whether longer-term dual antiplatelet therapy reduces the risk. We present a rare case of simultaneous very late DES thrombosis in the three vascular territories, following discontinuation of antiplatelet therapy seven years after stent placement, presenting as cardiogenic shock.